1995
DOI: 10.1152/ajpgi.1995.269.6.g867
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of epidermal growth factor occurs through the gastrointestinal tract and oral cavity in adult rats

Abstract: Introduction of radiolabeled epidermal growth factor (125I-EGF) by gavage or sublingual confinement resulted in a time-dependent uptake and systemic organ dissemination in the adult rat. Intact EGF was recovered primarily from the tongue, parotid, and sublingual/submandibular glands after administration by sublingual lozenge, whereas gastrointestinal administration resulted in 125I-EGF recovery primarily from plasma, stomach, and lung. Recovered radiolabeled EGF retained the ability to bind to the EGF receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…It was reported that absorption of a substantial amount of EGF occurs through the mucosa of the oral cavity in adult rats [31]and the excision of salivary glands aggravates experimental gastric ulcers [15, 17], but in our present study we could not find any strong evidence for aggravation of pancreatitis after salivectomy. The data obtained are not consistent.…”
Section: Discussioncontrasting
confidence: 95%
“…It was reported that absorption of a substantial amount of EGF occurs through the mucosa of the oral cavity in adult rats [31]and the excision of salivary glands aggravates experimental gastric ulcers [15, 17], but in our present study we could not find any strong evidence for aggravation of pancreatitis after salivectomy. The data obtained are not consistent.…”
Section: Discussioncontrasting
confidence: 95%
“…While it is possible that HB-EGF exerted its effect in our model via absorption into the bloodstream, it is also possible that it acted locally via direct contact with enterocyte EGFR. The gastrointestinal absorption of HB-EGF has never been reported; however, absorption of EGF was demonstrated after oral administration in suckling rats [44] and gastric or oral administration in adult rats [45]. Future experiments are needed to address the intestinal absorption of HB-EGF.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue distribution of 125 I–EGF was previously examined in mice, pigs and rats [33,41,42]. After oral administration of 125 I‐EGF in rats, the radioactivity in tissues reached a maximum by 30 min and declined thereafter [35]. At 2.5 min after intravenous injection of 125 I‐EGF, the highest fraction of injected radioactivity determined was found in liver (52%) followed by kidney (14%), small intestine (11%), skin (7%), spleen (0.8%) and lung (0.6%) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted to examine the plasma pharmacokinetics of EGF after topical,[31] subcutaneous,[32] oral,[33,34] sublingual,[35] rectal[36] and intravenous[36–40] administration in rats, mice and dogs. Tissue distribution studies have also been performed in rats, pigs and mice by determining total radioactivity after intravenous, oral and sublingual administration of 125 I‐EGF [33,41,42].…”
Section: Introductionmentioning
confidence: 99%